The role of irisin, adropin, ctrp-3 in the development adverse cardiac events following an acute myocardial infarction in patients with obesity - Koteliukh, Mariia; Котелюх, Марія Юріївна (My University, 2020)
Irisin has been shown to have protective effects against lung and heart damage. However, whether irisin affects acute myocardial infarction (AMI) with concomitant obesity remains unclear. Adropin is a peptide hormone that is involved in maintaining insulin sensitivity and is a new regulator of endothelial cells. CTRP3 is regulatory protein which can effected on the development of adverse cardiac events following an AMI with concomitant obesity.
Keywords: miocardial infarction; obesity